The Development Standard Agreement Influences on National and International Business Practices - Cindawati Cindawati (Hasanuddin Law Review, 2016)
The rapidly growing business traffic either nationally or internationally forces the business practices to establish a standard agreement to secure the products and to protect the buyer from any risks. The standard agreement successfully meets the demand of international trade which urgently need the high speed and the accuracy. The objective of this research is to find out how does the development of agreement affect to the commerce practices and what are the requirements of standard agreement in accordance with the right and obligation. A qualitative method is applied in searching data of business practices. This study uses a normative research which guides the rule of law or determines some business standards and norms. The finding of this study show that the development of agreement strongly affects to the commerce practices, and standar agreement is urgently needed by business practices as a guideline to perform business traffic as smooth as buyer and seller expect, then both seller and buyer should know the three alternative way used as the procedures of standard agreement, namely; contract signing, notification document agreement, and notification by bulletin board. At last, a standard agreement could be accepted as legal agreement corresponding to willingness and trustworthy.